Regional Inclusive Green Growth in Indonesia: Unraveling Determinants and Disparities - Asyrof, Rifqi Aqil; Rizaldi , Muhammad (Purnomo Yusgiantoro Center, 2025)
This research develops a regional framework for inclusive green growth in Indonesia and assesses the efficiency of government expenditure in driving it. Using cross-sectional data from 33 provinces in 2021, the study constructs an Inclusive Green Growth Index (IGGI) based on economic growth, social equity, and environmental sustainability, following the Asian Development Bank’s framework. Data Envelopment Analysis (DEA) is employed to evaluate government spending efficiency. This study fills a research gap by providing a standardized tool to measure economic inclusivity and sustainability at the regional level. Additionally, it introduces a novel approach by analyzing budget efficiency in promoting inclusive green growth across provinces. Findings reveal significant regional disparities, with Papua and Nusa Tenggara Barat lagging while Kalimantan Timur and DKI Jakarta lead. Inefficient government spending is identified as a key factor, though some regions, such as East Kalimantan and East Java, demonstrate better resource utilization. This research contributes by encouraging local governments to integrate IGGI into policy planning. The index helps the central government identify regional disparities and formulate equitable development strategies. Additionally, it emphasizes optimizing government financing for inclusive and sustainable economic programs, providing insights for improving policy effectiveness.